Pengaruh Kinerja Keuangan dan Good Corporate Governance terhadap Potensi Kebangkrutan Bank Muamalat Indonesia - Sinta Puspita Dewi; Iwan Setiawan; Ruhadi Ruhadi (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to examine the effect of financial performance and GCG variables represented by the presence of the Sharia Supervisory Board on the potential for bankruptcy of Bank Muamalat Indonesia. The type of data used is secondary data sourced from financial statements and corporate GCG reports using multiple linear analysis data analysis methods with data processing tools using EViews 10 software. The results of this study indicate that NPF has a significant negative effect, FDR has a significant negative effect, and CAR has a significant negative effect. significant positive on the potential for bankruptcy of Bank Muamalat Indonesia, then the presence of DPS also has a significant effect. positive effect in reducing the risk of bankruptcy.